Histomorphological patterns of skin adnexal tumours with an insight into molecular updates - A single institutional study - Sangeetha Kandasamy; Roopmala Murugan; Gramani Arumugam Vasugi; Kumudhini Priya Gunasekaran (Journal of Pathology of Nepal)
Background: Skin adnexal tumors are a spectrum of benign and malignant tumors that differentiate toward or arise from the adnexal unit of the skin. These rare tumors pose a challenge in diagnosis, and often, a discrepancy is seen between clinical and histopathological diagnosis.